Relationship Between Social Intelligence Level and Accentuations of Adolescents’ Character - Bodnar, A; Bodnar, E (KnE Life Sciences, 2018)
Introduction. The research is aimed at analysing the nature of the relationship between the social intelligence level and the type of accentuation of the personality of adolescents. This relationship is a problem because no fundamental research has been done on it, although its social significance is extremely high. After all, the weight of evidence suggests that personality accentuations are not simply connected with just social intelligence but perhaps are its determining factor. Social intelligence development provides a condition for success in both social adaptation and interpersonal interaction. This especially concerns adolescents, in whom accentuations determine both the way to overcome puberty crises—and acute affective reactions—and—especially—the situation in the system of interpersonal relationships. Methodology and methods. The comparative analysis is used. The authors compare the results of their own research into adolescents and school children aged 13–14 with the reference data. Specific empirical methods: Guildford’s social intelligence method, a modified questionnaire to identify the types of character accentuations among Lichko’s adolescents. Results. Adolescents with a labile and sensitive accentuation have a better ability to foresee the consequences of behaviour based on a real situation analysis. However, in the case of the labile type, this is due to adequate self-esteem, and in the case of the sensitive type this is due to the desire to avoid conflicts. An excitable type of accentuation adversely affects the level of development of the ability to assess the non-verbal behaviour. Adolescents with the demonstrative accentuation are able to better understand the speech expression of other people and correctly build their verbal behaviour. Among girls, the hypertemic and demonstrative accentuations are significantly more common than that in boys. Conclusion. Knowing the peculiarities of the interrelation between accentuations of the individual and social intelligence makes it possible to achieve the development of the latter by smoothing accentuations. Keywords: social intelligence, character accentuation, adolescence